Epidemiological link between canine monocytic ehrlichiosis caused by Ehrlichia canis and the presence of Rhipicephalus sanguineus sensu stricto in Argentina - Sebastian, Patrick Stephan; Mera y Sierra, Roberto; Neira, Gisela; Hadid, Jaled; Flores, Fernando Sebastian; Nava, Santiago (Springer, 2021)
In this work, we analyze data that support an epidemiological link between cases of canine monocytic ehrlichiosis (CME) by Ehrlichia canis and the presence of Rhipicephalus sanguineus sensu stricto as vector in an endemic area for this tick in Argentina. In a blood sample of a 1-year-old toy poodle with CME compatible clinical signs, which showed CME typical morulae in monocytes in Giemsa-stained blood smear, DNA of E. canis was detected by PCR. Further, DNA of E. canis was also detected in a female of R. sanguineus s.s. collected on the infected dog. Rhipicephalus sanguineus s.s. is the only member of the R. sanguineus group that prevails in the study area. The results of this study suggest that R. sanguineus s.s. may play a more important role in the transmission of E. canis than it was assumed so far. The epidemiological link between CME cases and R. sanguineus s.s. as vector in temperate areas of Argentina described in this work contrast previous studies which found that R. sanguineus sensu lato “tropical lineage” (which is absent in the study area) is competent to transmit E. canis but not R. sanguineus s.s.